Phase microstructure and morphology evolution of MgO-PSZ ceramics during the microwave sintering process. Issue 11 (1st June 2021) - Li, Qiannan; Ling, Yeqing; Zheng, Hewen; Chen, Guo; Chen, Jin; Koppala, Sivasankar; Jiang, Qi; Li, Kangqiang; Omran, Mamdouh; Gao, Lei
Abstract: In the present study, controllable microwave sintering was applied to prepare partially stabilised zirconia ceramics with enhanced phase composition and a more uniform structure. To reveal the phase interface properties and structural changes of PSZ ceramics during the microwave sintering process, XRD, FT-IR, Raman, and SEM characterisations were utilised. XRD analysis and Raman analysis demonstrated that the increase of sintering temperature promoted the martensite conversion. However, prolonging duration time was unconducive to the retention of the stable phase. Additionally, the FT-IR characteristic peak movement caused by the reversible phase martensite transformation was observed. Furthermore, SEM analysis found that microwave treatment improved the grain size and structure distribution of the as-received MgO-PSZ sample. This work constructed a controllable technical prototype of preparing PSZ ceramics via microwave sintering, which can provide a theoretical basis and experimental basis for further industrial production.